Pengembangan Lembar Kerja Murid untuk Melatihkan Kemampuan Berpikir Kritis pada Materi Laju Reaksi melalui Model Pembelajaran Inkuiri - Diah Ayu Apriliasari; Bertha Yonata (Chemistry Department, Universitas Negeri Manado, 2026)
Critical thinking ability is one of the 21st century skills that need to be trained, but students' critical thinking ability on reaction rate material is still relatively low. This study aims to develop a Student Activity Worksheet (LKM) through an inquiry learning model that is suitable for training the KBK on reaction rate material reviewed through the aspects of validity, practicality, and effectiveness. This study focuses on four KBK indicators, namely interpretation, inference, analysis, and evaluation. This study uses the ADDIE model which is limited to the Develop stage. The target of the pilot implementation is 29 students of grade XI of SMA Negeri 19 Surabaya. The results of content validation obtained a mode of 5 and construct validation obtained a mode of 4. The results of practicality based on student responses were 92.6% and student relevant activities were 96.61% and 97.73% in two meetings. The N-Gain Score results showed that 27 students obtained the high category and 2 students the medium category. The N-Gain Score results on the interpretation indicator were 0.95; inference 0.97; analysis 0.85; and evaluation 0.69. The results of the study show that the LKM developed is suitable for use.